Single precursor route to efficient cobalt sulphide counter electrodes for dye sensitized solar cells. (1st January 2015) - Congiu, M.; Albano, L.G.S.; Decker, F.; Graeff, C.F.O.
Graphical abstract: ABSTRACT: In this work a novel preparation method is proposed for the one step synthesis and thin-film deposition of cost effective counter electrodes for dye sensitized solar cells (DSSC). This method is fast and allows depositing CoS nanoparticles onto F-doped SnO2 (FTO) substrates within 2 hours. The cost of reagents needed is significantly less than the cost of the products based on hexachloroplatinic acid used in the production of platinum transparent counter electrodes, and the method is compatible with the ink-jet and screen-printing technologies. The whole process does not require expensive equipment and is of simple implementation. Electrochemical Impedance Spectroscopy, Cyclic Voltammetry and I-V curves under simulated sunlight were used to characterize the electrode efficiency and stability. The counter electrodes prepared according to our procedure were transparent and show good catalytic activity with the I-/I3 - redox couple in a high stability electrolyte for DSSC (HSE). Under the best deposition conditions the charge transfer resistance of the electrodes was 1.3 Ωcm 2, less than that of the screen printed platinum on FTO glass (2.3 Ωcm 2 ). Power conversion efficiencies up to 6.6% were reached using the CoS counter electrodes. The optimized CoS counter electrodes were demonstrated to work also with a ferrocene besed redox liquid electolyte.